Informing the Fact: Inuit Traditional Knowledge Contributes Another Perspective - Zamparo, JoAnne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary This paper discusses the differences between Inuit traditional knowledge and western science views, and presents a perspective designed to bring these two world views together. This is believed to be a highly desirable approach for the successful conduct of research and resource management projects on Inuit lands. Each world view has something to contribute to the other. Distinctions between indigenous (including Inuit) traditional knowledge and western science are identified using examples from wild-life resource management. These examples pinpoint issues that have emerged f rom previous attempts to integrate indigenous traditional knowledge with western science. These examples also provide insight into the elements necessary to facilitate a constructive working relationship between indigenous people and western scientists. The perspective presented synthesizes these elements to suggest the means to achieve constructive working relationships between Inuit people and practitioners of western science.